Impaired olfactory function in patients with polycystic ovary syndrome. Issue 6 (1st June 2016) - Koseoglu, Sezen Bozkurt; Koseoglu, Sabri; Deveer, Ruya; Derin, Serhan; Kececioglu, Mehmet; Sahan, Murat
Abstract: Polycystic ovary syndrome (PCOS) is an endocrine disorder which affects 6.6% of women of child‐bearing age. Although olfactory dysfunction is frequent in the population and it negatively affects quality of life, neither physicians or patients consider this important. This case‐control study included 30 patients diagnosed with PCOS, and 25 healthy age‐matched controls. Sniffin' sticks tests (BurghartGmbH, Wedel, Germany) were used to analyze olfactory functions, and the Beck Depression Inventory was used to evaluate depressive symptoms. The total odor score was significantly lower in the PCOS group compared to the control group ( p < 0.005). The Beck depression score was higher in the PCOS group ( p < 0.005). There was a negative correlation between the total odor score and the Beck Depression Score. Patients with PCOS have impaired olfactory function. This might be related to depressive disorders that are also observed in those patients.